Supercritical CO$_2$ Technology in Resource-effective Production of Functional and Smart Textiles (Journal of Fiber Bioengineering and Informatics, 2023)
The purpose of this work was to investigate the potential application of scCO2 dyeing technology to produce functional and smart textiles. Selected dyes and functional agents were applied to polyester fabric using the scCO2 impregnation technique. The effects of the processing variables on the functional and colour performances were explored. The results showed that scCO2 is a viable technique to produce functional polyester fabric in a resource-efficient and eco-friendly way. Dyed polyester fabric with additional functionalities such as antimicrobial, antioxidant, UV protection, and UV sensing properties were realised. The fabrics developed have demonstrated desirable colour and functional properties without affecting each other confirming compatibility. Moreover, the functional fabrics exhibited the required durability and fastness properties sufficient for various applications. This research project contributes towards widening the application of the supercritical CO2 dyeing technique and paves a way for sustainable production of functional and smart textiles in a resource-efficient and eco-friendly way.
Keywords: Supercritical CO$_2$; Functional and Smart textiles; Antimicrobial; Antioxidant; UV protective textile; Textile UV-sensor; Curcumin natural dye; Chitosan biopolymers; Photochromic textiles